The Effect of Imbalance On Rotor Vibration in Electric Motors - Albaru, Agung; Balqis, Dinda; Afriandi, Irvan; Syaputra, Muhammad Lyan (METALOGRAM, 2025)
Mechanical system failures in electric motors are often caused by mass imbalance in the rotor. This imbalance occurs when the mass distribution is uneven relative to the axis of rotation, causing the center of mass to deviate from the rotational axis. Such conditions generate centrifugal forces that lead to excessive vibrations, accelerate component wear, reduce efficiency, and shorten the motor’s lifespan. Mass imbalance in the rotor system is one of the main causes of excessive vibration in rotating machines, which can result in performance degradation, component wear, and even catastrophic failure. This study aims to analyze the vibration characteristics caused by unbalance in a single rotor and evaluate the effectiveness of the trial weight balancing method (three-test-mass method) in reducing the resulting vibrations. Experimental testing was conducted using a Digital Signal Analyzer (DSA), an accelerometer sensor, and a rotor test system with various unbalanced mass configurations installed on the rotor disk. Vibration data were analyzed in both time and frequency domains using the Fast Fourier Transform (FFT) to identify dominant frequencies due to unbalance. The results show that the highest vibration amplitude occurs at the fundamental frequency corresponding to the rotor’s rotational speed. The three-test-mass balancing method proved effective in significantly reducing the vibration amplitude after mass correction. These findings indicate that identifying unbalance through vibration response and applying an appropriate balancing method can improve the stability and reliability of rotating rotor systems, including both three-phase induction motors and universal motors such as electric drills.